Comparative study of Inconel 601, 625, 718, 825 super-alloys during Electro-Discharge Machining. (2022) - Mohapatra, Shivam; Rahul,; Kumar Sahoo, Ashok
Abstract: In this review paper, I have tried to do a comparative study of chemical, mechanical properties of Inconel 718, 625, 825 and 601. The machinability of the different grades of super alloys are also discussed using EDM. Inconel super alloys are nickel based super alloys, which are light in weight but are very robust in nature and have the high creep in wide variety of temperature. It has found its application predominantly in manufacturing industries like in marine, automotive and aerospace industries.